Partisipasi Gender dalam Pengelolaan Subak Taman Bali, Desa Sidan, Kecamatan Gianyar Kabupaten Gianyar - DAMAYANTHI, I DEWA AYU OKA; ASTITI, NI WAYAN SRI; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Gender Participation In The Management of Subak Taman Bali, Sidan Village, Gianyar Sub District, Gianyar Regency One of the efforts made to develop agriculture is to maintain the continuity of subak management carried out by all members. In fact, the push for gender equality influences agricultural activities, especially the management of the Taman Bali Subak. This study aims to find out how gender participation is in the management of Subak Taman Bali by linking it to the allocation of work time for each gender. The results showed that all members of Subak Taman Bali participated in the management of subak. Women are more dominant in organizing ritual activities with a HOK value of 61.1 HOK. Men are more dominant in activities that require more energy and more knowledge in agriculture such as the search and distribution of irrigation water with a HOK value of 10.7 HOK, operation and maintenance of facilities with a HOK value of 134.2 HOK, mobilization resources and fund extraction with a HOK value of 1.5 HOK, handling disputes or conflicts with a HOK value of 10.7 HOK and innovation adoption activities with a HOK value of 10.7 HOK. Based on the results, it can be seen that women still have less time allocation than men do in managing subak and gender inequality still occurs. It is expected that they should understand more about gender equality so that it does not differentiate men and women especially in the field of ability so that each member has the same opportunity to be able to participate more in managing the Subak Taman Bali.